A giant uterine tumor in a woman with myotonic dystrophy. Issue 4 (23rd February 2017) - Kataoka, Hiroshi; Ueno, Satoshi
Key Clinical Message: Patients with myotonic dystrophy are at particularly high risk for cancer arising in the endometrium, brain, colon, or ovary. Giant leiomyoma can occur in patients with myotonic muscular dystrophy, a disease accompanied by muscle wasting. Abstract : Patients with myotonic dystrophy are at particularly high risk for cancer arising in the endometrium, brain, colon, or ovary. Giant leiomyoma can occur in patients with myotonic muscular dystrophy, a disease accompanied by muscle wasting.